Village Finance and Community Institution Training in East Lumban Pea Village, Toba Regency - Sagala, Farida; Normi, Siti; Simanjuntak, Arthur; Siahaan, Septony B.; Ginting, Mitha Christina; Sagala, Lamria; Goh, Thomas Sumarsan; Panjaitan, Rike Yolanda; Situmorang, Duma Rahel; Simanjuntak, Faido M.P.; Rajagukguk, Tiur; Gultom, Robinhot; Sianturi, Jeudi A.T.P.; Siregar, Jeremia; Nadeak, Heri (Indonesian Journal of Advanced Social Works, 2023)
The purpose of this training is to increase the accounting knowledge of village heads and village officials so that they can record village financial transactions properly and accurately. There are several stages in conducting philanthropy: preparation, implementation, evaluation, and reporting. Findings from interviews with village heads and village officials regarding village financial management include: Planning Stage: At this stage, village heads and village organizations identify local problems and respond to community suggestions through the Village Consultative Body (BPD) and community leaders. Implementation Stage: After the activity implementation file is complete, the activity implementation file is ready to be submitted. Administration Stage: The treasurer must report how much his income and expenses are and detail what the funds are used for. Reporting Stage: At the reporting stage, the village treasurer is responsible and obliged to record and book properly account for money through financial accountability reports at the end of each month. Accountability Stage: The village head is basically responsible to the residents and the accountability process is passed through the Camat to the Regent/Mayor.